Application of endobronchial ultrasound-guided transbronchial needle aspiration for re-biopsy in lung cancer - Kabalak, Pinar Akin; Kizilgoz, Derya; Yilmaz, Ulku; Demirag, Funda (Annals of Medical Research, 2021)
Aim: The initial mutation status of non-small cell lung cancer (NSCLC) is important for guiding treatment. However, re-biopsy is needed to determine the new mutation status in patients receiving targeted therapy or who develop resistance during first-line therapy. Endobronchial ultrasound (EBUS) is an important tool to obtain adequate tissue for molecular analyses. Materials and Methods: We used a clinical database of 349 patients who were previously included in a multi-center study. Adequacy of tissue collected, new molecular profile, and treatment regimens were evaluated.Results: A total of 50 patients (median age of 60 ± 9 years) received biopsy by EBUS. The success rate was 36% (n = 18), and repeat re-biopsy was performed for patients with anthracosis (n = 32). In 18 patients, only one lymph node station was sampled. Initial histopathology was adenocarcinoma in 28 patients, squamous cell carcinoma (SCC) in 18 patients, and not otherwise specified (NOS) in four patients. No correlation was found between initial treatment type and success rate of the procedure (p = 0.101). After re-biopsy in six patients (five of whom had newly detected mutations), targetable mutations were detected for T790M (n = 2), EGFR-exon 19 (n = 1), c-Met (n = 1), and EGFR-21 (n = 2).Conclusion:  In cases of resistance to treatment, re-biopsy should be performed to detect different gene amplifications. Re-biopsy with EBUS is an effective method for an appropriate progressive lesion.
Keywords: Endobronchial ultrasound (EBUS); lung cancer; re-biopsy